2013
DOI: 10.1177/0957650913495385
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady wall pressure measurement in a one-and-a-half stage axial transonic compressor during stall inception

Abstract: This paper presents the experimental investigation of the stall inception of a state-of-the-art transonic compressor that resembles a typical front stage of a commercial jet engine. The compressor was designed and manufactured in cooperation with Rolls-Royce Deutschland and assembled in the Darmstadt Transonic Compressor test facility at Technische Universität Darmstadt, Germany. Utilising the 1.5-stage design it is possible to investigate stall inception for different rotor inflow conditions. The aerodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Yamada et al 14 suggested that the periodic breakdown of the TLV resulted in self-sustained flow oscillation in the tip leakage flow field. Biela et al 15 suggested that the unsteadiness of the flow in the tip region was mainly caused by TLV oscillation with the frequency of around 0.5 BPF. Du et al 16 suggested that the momentum ratio between the main flow and the TLF can be one of the factors that dominate the self-induced unsteadiness in the tip region.…”
Section: Introductionmentioning
confidence: 99%
“…Yamada et al 14 suggested that the periodic breakdown of the TLV resulted in self-sustained flow oscillation in the tip leakage flow field. Biela et al 15 suggested that the unsteadiness of the flow in the tip region was mainly caused by TLV oscillation with the frequency of around 0.5 BPF. Du et al 16 suggested that the momentum ratio between the main flow and the TLF can be one of the factors that dominate the self-induced unsteadiness in the tip region.…”
Section: Introductionmentioning
confidence: 99%
“…Through the measurement of pulsation of the axial velocity in a single-stage axial compressor, Mcdougall [12] first discovered the model type stall inception characterized by large-scale disturbance, smaller rotation speed, and lack of specific time and origin of space. In recent years, relevant researches at home and abroad have shown that the adjustment of structural and operating parameters can change complex flow fields in flow passages, affecting the forms of stall inception [13,14]. Bianchi S et al [15] conducted an experimental study on stall inception patterns under different installation angles of rotor blades in a low-speed axial fan.…”
Section: Introductionmentioning
confidence: 99%
“…Spikes rotate at 70–80% of the rotor speed, and the time between the first detection of a spike and the formation of a large stall cell is less than five rotor revolutions, much shorter than the time of evolution of the modal-type inception. 7–13…”
Section: Introductionmentioning
confidence: 99%